A Brief Note on Coherent Feedback in Semiconductor Lasers - M. A. Grado Caffaro; M. Grado Caffaro (Active and Passive Electronic Components)
Some aspects on coherent feedback in a laser diode are investigated. In particular, weak optical feedback is considered in the context of the feedback-induced frequency shift. In addition, the Lang-Kobayashi equations are considered.